PERBEDAAN EFEKTIVITAS PROPRIOCEPTIVE EXERCISE DAN ZIG-ZAG RUN EXERCISE TERHADAP PENINGKATAN KELINCAHAN PADA ANAK USIA 9-11 TAHUN DI SEKOLAH DASAR NEGERI 4 SANUR - Made Dwi Indah Permatahati Gita; Ni Luh Nopi Andayani; I Wayan Sugiritama; Ida Ayu Dewi Wiryanthini (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2016)
ABSTRACTAgility is a person's ability to change the direction and position of the body quickly, effectively, and accurately in a short time without any sign of losing balance. This study with Pre and Post Test Two Group Design aims to compare Proprioceptive Exercise and Zig-zag Run Exercise in improving the agility of children aged 9-11 years in Elementary School 4 Sanur. The amount of samples is 16 children that divided to 2 groups. The average difference in agility improvement on the Proprioceptive Exercise group was 3.46 seconds and Zig-zag Run Exercise group was4.98 second with independent sample T-test result obtained p=0.003 (p<0.05). It can be concluded that Zig-zag Run Exercise is better for improving agility than Proprioceptive Exercise of children aged 9-11 years in Elementary School4 Sanur. Keywords: Agility, Proprioceptive Exercise, Zig-zag Run Exercise, Shuttle Run Test.